2020
DOI: 10.1126/sciadv.aaz0525
|View full text |Cite
|
Sign up to set email alerts
|

Computational and experimental performance of CRISPR homing gene drive strategies with multiplexed gRNAs

Abstract: The rapid evolution of resistance alleles poses a major obstacle for genetic manipulation of populations with CRISPR homing gene drives. One proposed solution is using multiple guide RNAs (gRNAs), allowing a drive to function even if some resistant target sites are present. Here, we develop a model of homing mechanisms parameterized by experimental studies. Our model incorporates several factors affecting drives with multiple gRNAs, including timing of cleavage, reduction in homology-directed repair efficiency… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(129 citation statements)
references
References 40 publications
2
115
0
Order By: Relevance
“…Perhaps most importantly, TA systems should be far less vulnerable to the formation of resistance alleles than current CRISPR homing drives. Even though multiplexing can somewhat ameliorate the formation of the more critical r1 alleles in homing drives, this typically comes at the cost of reduced drive efficiency due to a variety of factors involved in homology-directed repair [18,27]. For homing drives designed for population modification, it would also be necessary to target essential genes to remove resistance alleles that disrupt the target function [28], which would open up the possibility for incomplete homology-directed repair to form r1 alleles, possibly at rates that would preclude success of the drive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps most importantly, TA systems should be far less vulnerable to the formation of resistance alleles than current CRISPR homing drives. Even though multiplexing can somewhat ameliorate the formation of the more critical r1 alleles in homing drives, this typically comes at the cost of reduced drive efficiency due to a variety of factors involved in homology-directed repair [18,27]. For homing drives designed for population modification, it would also be necessary to target essential genes to remove resistance alleles that disrupt the target function [28], which would open up the possibility for incomplete homology-directed repair to form r1 alleles, possibly at rates that would preclude success of the drive.…”
Section: Discussionmentioning
confidence: 99%
“…This is not only because we assumed a high proportion of repair resulting in r1 sequences, but also because the possibility for simultaneous cutting was not included in our deterministic model. However, such events should take place quite often, particularly as the number gRNAs increases because even one instance of simultaneous gRNA cleavage would likely cause a large enough deletion to prevent formation of an r1 allele [18,27]. Additionally, homologydirected repair of drive cleavage using disrupted alleles as a template would likely preclude the formation of r1 alleles, and this was not taken into account in our model.…”
Section: Resistance To Ta Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to multiplexing gene drives to recognise more than one target site [ 3 , 4 , 11 , 12 ], akin to combination therapy with antibiotics, it is necessary to reduce the relative contribution of the error-prone end-joining repair pathway, over HDR, since this can serve to increase the range and complexity of potential resistant alleles on which selection could act.…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary to early suspicions that all possible target sites would be prone to such mutations (e.g., Drury et al 2017), at least one essential genomic site has been identified in mosquitoes that is intolerant of mutations and thus appears to escape this problem (Kyrou et al 2018). Furthermore, CRISPR-based gene drives can be designed to cut at multiple sites in the same gene (any of which suffice to allow the drive to function), thus ameliorating most concerns about the inevitability of target-site resistance (Oberhofer et al 2018; Champer et al 2018, 2020c). Other forms of resistance to CRISPR-based gene drives are theoretically possible, but it is too early to tell whether they will prove to interfere with implementations: inbreeding, proteins that block CRISPR complex activity, and suppressors of CRISPR gene expression (Stanley and Maxwell 2018; Bull et al 2019).…”
Section: Introductionmentioning
confidence: 99%